Gnosticism in the Words of Sheikh Mahmoud Shabestari - Nezhad, Mousa Rahimi; Pazhohandeh, Seyed Jasem (Journal of History Culture and Art Research, 2017)
This article attempts to deal with Gnosticism in the words of Sheikh Mahmoud Shabestari in addition to investigating the mystical themes and philosophical works of him. It can be claim that Sheikh Shabestari made the best and finest Gnostic and theological implications into poetic form. He was impressed by three philosophical-theological schools including the philosophy of Ibn Arabi, the theological school of Ash’ari and the romance of Sanaee. The first part of the study focuses on the Gnostic concepts and terms in the words of Sheikh Shabestari. In the following sections, we discuss the Gnostic concepts and the theory of pantheism in the words of Sheikh. Gnosticism in the words of Sheikh Mahmoud Shabestari, is one of the most important issues in the field of Gnostic mainstreaming in the speech of philosophers and famous mystics of Islam. To understand Gnosticism in the words of Sheikh Mahmoud Shabestari, it is necessary to philosophically investigate and analyze schools and Gnostic and philosophical movements before him which have influenced him. Therefore, in this study we have tried to talk about schools influencing him in addition to describing Gnosticism in the words of Sheikh Mahmoud Shabestari. Apart from this, we investigate how the Gnosticism of Sheikh Shabestari revolves around a main idea that is pantheism.